Perlindungan Hukum Kepada Pemegang Merek Terhadap Adanya Barang Tiruan - Astri Maharani; Ayesta Intania; Cahyo Danang Prayugo; Real Figo Pratama; Sartika Puspa Sekar Arum (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Brand building has an important role in the world of trade. Protection of registered goods brand rights holders from unlawful acts committed against registered goods marks as unfair competition efforts such as imitation, counterfeiting or use of marks without rights to certain brands. This is of course detrimental to brand holders and consumers. The results of the research show that forms of protection for brand holders can be through preventive and repressive efforts. The aim of this research is to determine the legal protection for brand rights holders for the sale of counterfeit goods and to determine the efforts of brand holders to overcome the large number of counterfeit goods. The research method used is normative juridical with a qualitative approach, namely by collecting various kinds of data.